True crime stories - Deary, Terry (Hippo, 1994)
Nine compelling crime stories full of suspense, daring and intrigue. a terrifying siege ends when two brave citizens bring the infamous Ned Kelly to justice at last. A bloody clue under the floor helps an ingenious detective to identify a brutal murderer. And a game of Monopoly played with real money leads to the exposure of the Giant Train Robbers.